Troubled normalities: “Living on” and “living with” HIV in the treatment possibility era - Sofika, Dumisa (PINS-Psychology in Society, 2025)
Squire, Corinne (2013) Living with HIV and ARVs: Three-letter lives. Houndmills: Palgrave Macmillan. ISBN 978-0-230-28423-4 hbk. Pages vi + 275. In Living with HIV and ARVs: Three-letter lives, Corinne Squire delves into very touching issues related to living with HIV in the treatment possibility era and what some have come to call the era of a possible AIDS free generation. Conducted in two settings, the UK and South Africa, the author looks at how HIV has come to be naturalized (seen as a natural, manageable and understandable part of our everyday biological, social and economic environments). This naturalization has been brought about by the medicalization of HIV, which because of scientific and medical breakthroughs in HIV, sees ARV treatment as especially important to the treatment and management of HIV. Naturalization also occurs through the normalization of HIV, where HIV is presented as a regular and unproblematic part of everyday health and social relations, and through marketisation where participation in market economies has been presented as a solution to living a normal healthy HIV lifestyle for the HIV positive.